The Effect of Dysmenorrhea on the Sleep Quality of YARSI University’s Medical Student Batch 2020 According to Islamic Perspective - Nabilla Rizqina Rachmaputri; Endang Purwaningsih; Qomariyah Qomariyah; Firman Arifandi (Junior Medical Journal, 2022)
Background: Dysmenorrhea is the most common gynecological problem in women and is defined as pain and cramping in the lower abdomen that occurs before or during menstruation. Dysmenorrhea is a condition that significantly affects women's quality of life such as interfering with daily activities and also experiencing sleep problems. This is related to the quality of a person's sleep. Good quality sleep is adequate sleep and does not show signs of sleep deprivation and does not experience sleep problems.Methods: This study aims to determine the effect of dysmenorrhea on sleep quality in students of the Faculty of Medicine, YARSI University Batch 2020.Methods: This type of research is descriptive analytic with a cross-sectional study approach. The sample in the study were students of the Faculty of Medicine, YARSI University class of 2020 with 117 respondents. Data was collected by filling out a questionnaire to measure pain and sleep quality, namely the Numeric Rating Scale (NRS) and the Pittsburgh Sleep Quality Index (PSQI). Statistical analysis using Chi-Square test. Results: The results showed that 25 people (51%) experienced mild dysmenorrhea with good sleep quality, 9 people (20.5%) experienced moderate dysmenorrhea with good sleep quality, and 2 people (8.3%) experienced severe dysmenorrhea with sleep quality is good. There were 24 people (49%) experiencing mild dysmenorrhea with poor sleep quality, 35 people (79.5%) experiencing moderate dysmenorrhea with poor sleep quality, and 22 people (91.7%) experiencing severe dysmenorrhea with poor sleep quality. The results of the Chi-Square analysis showed that there was an effect of the incidence of dysmenorrhea on sleep quality.Conclusion: There is an effect of the dysmenorrhea with sleep quality in students of the Faculty of Medicine, YARSI University Batch 2020.